A LINGUISTIC CATEGORY ANALYSIS OF GRAMMATICAL ERRORS IN THE SPEAKING OF SENIOR HIGH SCHOOL STUDENTS IN BONE REGENCY - Dewi Fatma Riana; Hidayat, LD. Dian; Wahyu; Hasriati Nur (PT Akselerasi Karya Mandiri, 2025)
This study aimed to identify the types and causes of grammatical errors in students’ speaking performances, analyzed using the linguistic category framework. A qualitative descriptive method was employed, with data collected through a speaking test (in a question-and-answer format) and interviews. Participants were selected through judgmental sampling and consisted of one English teacher and ten second-year students from a senior high school in Bone Regency, South Sulawesi, Indonesia. The grammatical errors were categorized into two main types: morphological and syntactical. Morphological errors included mistakes in the use of inflections, articles, prepositions, and pronouns, with pronoun and article misuse being the most frequent. Syntactical errors involved incorrect usage of copulas, subject-verb agreement, adjective order, and tenses, with tense-related errors occurring most commonly. The analysis also revealed several contributing factors to these errors, including students’ difficulty in understanding and internalizing grammar rules, limited exposure to correct grammatical forms, insufficient speaking practice, and low motivation to engage in grammar-based speaking activities. These findings underscore the importance of more targeted and engaging grammar instruction in speaking-focused English learning environments.